(untitled) (World Science, 2023)
Modern Ukrainian female servicemen from the temporarily occupied territories and other regions of Ukraine in the conditions of martial law have serious risks for deterioration not only of their health, but also of future children, which is due to the negative effects of stress factors during the war. Among which there are unfavorable working conditions of military personnel (severe neuropsychic tension, violation of the diet and sleep, increased physical activity, hypothermia; inappropriate living conditions, life and activity of personnel, problems of obtaining gynecological care; ), as well as environmental conditions: chemical factors (substances that pollute water and air: gunpowder, accumulator gases, combustion products, heavy metals, engine maintenance products, aerosols, pesticides, anthropotoxins), physical factors (noise, vibration, extreme temperature regimes, height, radiation), environmental factors, etc. It is worth noting that at present one of the key factors of disruption of the functioning of the body is post-traumatic stress disorder. According to current data, about 30% of people affected by traumatic events will have PTSD and need help. As for the female population, during the life of PTSD is diagnosed in about 10% of adult women and 7% of girls. It is also known that in women, manifestations of PTSD are observed almost 1.5 times more often than in men. Particularly high level of prevalence of mental disorders is noted among internally displaced persons. In particular, in this cohort, PTSD develops and is diagnosed in 22% of men and 36% of women. Among the symptoms of PTSD, depression (in 16 and 25%, respectively) and anxiety (in 13 and 20%, respectively) are most common.